Cytokine Cocktail Promotes Alveolar Macrophage Reconstitution and Functional Maturation in a Murine Model of Haploidentical Bone Marrow Transplantation - Hong, Chao; Lu, Hongyun; Jin, Rong; Huang, Xiaohong; Chen, Ming; Dai, Xiaoqiu; Gong, Fangyuan; Dong, Hongliang; Wang, Hongmin; Gao, Xiao-Ming (Frontiers in Immunology, 2021)
Infectious pneumonia is one of the most common complications after bone marrow transplantation (BMT) which is considered to be associated with poor reconstitution and functional maturation of alveolar macrophages (AM) post-transplantation. Here we present evidence showing that lack of IL-13-secreting ILC2s in the lungs may underly poor AM reconstitution in a mouse model of haploidentical BMT. Recombinant murine IL-13 was able to potentiate monocyte-derived AM differentiation in vitro. When intranasally administered, a cocktail of GM-CSF, IL-13 and CCL2 not only promoted donor monoycte-derived AM reconstitution in haploidentical BMT recipient mice but also enhanced the innate immunity of the recipient animals against pulmonary bacterial infection. These results provide useful clue for a clinical strategy to prevent pulmonary bacterial infection at the early stage of recipients post-BMT.